Razão de prevalências: Alcoolismo nas diferentes regiões geográficas do Brasil segundo o sexo - Campos, Juliana Alvares Duarte Bonini [UNESP]; Loffredo, L. C M [UNESP]; Almeida, J. C. [UNESP] (My University, 2007)
The present study applies a method of prevalence analysis to data obtained in two nationwide household surveys on alcohol use during life and dependence, for each of the sexes. The ratios of prevalences (R), for the lifetime alcohol use and dependence rates, between the two genders in the various Brazilian macro-regions, were calculated together with their respective 95% confidence intervals. It was found that lifetime use, both in 2001 and in 2005, was significantly greater in Brazilian males in all geographical regions. In 2001, the population of the North (male and female) had a higher rate of alcohol consumption than that in the Brazilian population as a whole and that in the Southeast. Dependence on the consumption of alcoholic drinks in 2001 and in 2005 was greater in the male sex, but similar among the various regions studied. It can be concluded that this method of analyzing the data on alcoholism could be of great use in assessing its magnitude and importance in terms of public health.

O presente estudo apresenta uma metodologia de análise de prevalência, utilizando dados obtidos em dois levantamentos domiciliares com representatividade nacional, sobre uso na vida de álcool e dependência, segundo o sexo. Foi calculada a razão de prevalências (R), com seu respectivo intervalo de 95% de confiança, para as taxas de uso na vida de álcool e de dependência para os diferentes sexos, nas diferentes macro regiões brasileiras. Os resultados obtidos mostraram que o uso na vida de álcool, em 2001 e em 2005, foi maior entre os brasileiros do sexo masculino com diferença significativa em todas as localizações geográficas. Em 2001, a população da região Norte mostrou taxa de prevalência do consumo de álcool entre homens e mulheres acima do apresentado pelo Brasil como um todo e pela região Sudeste em particular. A dependência do consumo de bebidas alcoólicas em 2001 e em 2005 foi maior entre o sexo masculino e similar nas diferentes regiões estudadas. Pode-se concluir que a metodologia de análise aplicada aos dados sobre o alcoolismo pode ser de grande utilidade para conhecer sua magnitude e importância do ponto de vista da saúde pública
Use of prevalence ratio to analyze alcoholism among men and women in the various geographic regions of Brazil
Keywords: Alcoholism; Prevalence; Public health; Statistical methods; alcohol; alcohol consumption; alcoholism; Brazil; calculation; confidence interval; data analysis; female; geographic distribution; health survey; human; major clinical study; male; mathematical analysis; prevalence; sex difference; sex ratio